Three-dimensional multispecies nonlinear perturbative particle simulations of collective processes in intense particle beams - Hong Qin; Ronald C. Davidson; W. Wei-li Lee (Physical Review Special Topics. Accelerators and Beams, 2000)
Collective processes in intense charged particle beams described self-consistently by the Vlasov-Maxwell equations are studied using a 3D multispecies nonlinear perturbative particle simulation method. The newly developed beam equilibrium, stability, and transport (BEST) code is used to simulate the nonlinear stability properties of intense beam propagation, surface eigenmodes in a high-intensity beam, and the electron-proton (e-p) two-stream instability observed in the Proton Storage Ring (PSR) experiment. Detailed simulations in a parameter regime characteristic of the PSR experiment show that the dipole-mode two-stream instability is stabilized by a modest spread (about 0.1%) in axial momentum of the beam particles.